OBJECT-ORIENTED APPROACH TO IDENTIFYING THE RELEVANCE OF IT-EDUCATION TO THE LABOR MARKET DEMAND - Masuma H. Mamedova; Faik R. Mamedzade (Obrazovanie i Nauka)
The paper deals with the issues of human resources development and IT-staff training. The authors put a special emphasis on bringing the IT-staff training system in line with the labor market demands both in quantitative and qualitative terms. Based on the object-oriented approach, the authors explore the reasons behind the existing imbalance between the markets of IT-education services and IT-specialists in Azerbaijan, the challenges facing the IT education and specificity of the IT-specialists market being described.For overcoming the above gap between the IT labor market supply and demand, the authors put forward a model of professional competences, reflecting the real-life requirements for a specialist’s quality. Additionally, the paper outlines the recommended trends of IT-sector development in Azerbaijan, which include organization of innovative research and education centers for specialists’ training and retraining, legislative and institutional coordination of the IT industry and education, development of new educational standards, increase in the number of IT-profile students.